Makkovik, Schulkinder beim Holztransport : [19--] - Hettasch, Paul, 1873-1949. (2001)
Black and white photograph of Makkovik school children helping put firewood on sleds. Black and white photograph of Makkovik school children helping put firewood on sleds.